A Study on Reflections of Prophetic Sīrah Discourse in Pluralistic Society: A Contextual Analysis - Ashker Aroos; Mohamed Ashath; Fatmir Shehu (DIROSAT: Journal of Education, Social Sciences & Humanities, 2024)
This research explores the evolving debates on Prophetic Sīrah discourse within pluralistic societies, addressing the critical need for a comprehensive understanding among Muslims. Recognizing the fragmented nature of previous works, which often focus on isolated aspects of the Sīrah, this study aims to provide an integrated analysis relevant to contemporary multicultural settings. Employing a qualitative, library-based methodology, the research utilizes primary sources such as the Qur'an, Hadīth collections, and classical Sīrah texts, alongside modern commentaries. Through thematic and contextual analyses, key concepts like interfaith relations, social justice, and ethical conduct are identified and examined. Critical discourse analysis (CDA) is applied to understand how Sīrah discourse is constructed and communicated across different contexts. The study reveals significant gaps in the current understanding and application of the Prophetic Sīrah, particularly regarding its relevance for Muslim minorities in pluralistic societies. It emphasizes the importance of defining key terminologies and developing an interpretive framework that aligns with the minority context. The findings underscore the urgent need to reframe the Prophetic Sīrah from a pluralistic perspective to foster peaceful coexistence and mutual respect. The study concludes by attempting to bridge the gap between traditional Islamic teachings and modern pluralistic principles, encouraging a more inclusive and peaceful community.